Understanding the persistence of policy failures: The role of politics, governance and uncertainty. (July 2015) - Howlett, Michael; Ramesh, M; Wu, Xun
The persistence of policy failures is a recognized but not well-understood phenomenon in the literature of the policy sciences. Existing studies offer only limited insights into the persistence of policy failures as much of the literature on the subject to date has focused on conceptualizing the topic and differentiating between different types of failures. Much less attention has been paid to systematically examining the sources of the problems which lead to recurrent failures. Collectively, the articles in this issue move this discussion forward and show the persistence of policy failures can be better understood by examining a wide range of factors both within and beyond a policy subsystem, especially the nature of the political system and its influence on decision making, governance capacity and the impact of its limitations on the chances for policy success, and levels of uncertainty in policy knowledge and practice, which continue to plague decision making and decision makers.